Murine Asialo GM1(+)CD8(+) T Cells as Novel Interleukin‐12‐responsive Killer T Cell Precursors - Lee, Ushaku (Jpn J Cancer Res, 1996)
Freshly isolated CD8(+) T cells, but not CD4(+) T cells, contained 20–30% of asialo GM1(+) (ASGM1(+)) T cells which were distinct from ASGM1(+)NK1.1(+) natural killer cells. This novel ASGM1(+)CD8(+) T cell subpopulation showed a strong proliferative response to interlenkin‐12 (IL‐12) in the presence of IL‐2. Culture of ASGM1(+)CD8(+) T cells with IL‐12 plus IL‐2 allowed the generation of anomalous killer T cells concomitantly with the accumulation of cytolytic molecules. Moreover, ASGM1(+)CD8(+) T cells produced high levels of interferon‐γ (IFN‐γ), but not IL‐4, upon stimulation with IL‐12 plus IL‐2. Such immune responses were not observed in ASGM1(−) CD8(+) T cell snbpopulations constituting the majority of CD8(+) T cells. These results demonstrated that ASGM1(+)CD8(+) T cells are a novel subpopulation of IL‐12‐responsive and IFN‐γ‐producing killer T cell precursors.